Heavy-duty trucks: The challenge of getting to zero. (April 2021) - Giuliano, Genevieve; Dessouky, Maged; Dexter, Sue; Fang, Jiawen; Hu, Shichun; Miller, Marshall
Highlights: Battery electric heavy duty trucks are not yet good substitutes due to limited range and required charging times. Hybrid-electric vehicles offer opportunities for GHG reductions in the near term. Technology improvements will make battery electric trucks more competitive by 2030. Flexible policies that support multiple new technologies may best reduce heavy truck emissons. Abstract: This research considers strategies that will reduce truck emissions and achieve public health and GHG reduction targets. Freight shipments in urban areas are increasing throughout the world as a result of globalization, rising incomes, and shifting patterns of production and consumption. Urban freight shipments are overwhelmingly made by trucks, which generate significant negative impacts on human health and contribute to GHG emissions. We examine the potential of zero emission heavy-duty trucks (ZEHDTs). We use simulation modeling and case studies to explore the impacts of using battery electric heavy-duty trucks (BEHDTs) and natural gas hybrid heavy-duty trucks (hybrid HDTs) in freight operations, taking into account differences in performance and refueling. We estimate impacts for 2020, 2025, and 2030. BEHDT applications are limited in the near term due to range and charging limitations, but as BEHDT performance improves and prices go down, they are viable for a larger segment of the market. Hybrid vehicles are the most cost-effective alternative for reducing air toxics, but BEHDTs reduce air toxics the most by 2025. Subsidies and charging infrastructure investment would be required to promote use of BEHDTs.